2014
DOI: 10.1016/j.mvr.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Proline-rich region of non-muscle myosin light chain kinase modulates kinase activity and endothelial cytoskeletal dynamics

Abstract: Disruption of the pulmonary endothelial barrier and subsequent vascular leak is a hallmark of acute lung injury. Dynamic rearrangements in the endothelial cell (EC) peripheral membrane and underlying cytoskeleton are critical determinants of barrier function. The cytoskeletal effector protein non-muscle myosin light chain kinase (nmMLCK) and the actin-binding regulatory protein cortactin are important regulators of the endothelial barrier. In the present study we functionally characterize a proline-rich region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Recently, identical proteomic analyses of the plasma from rats that underwent hemorrhagic shock demonstrated that α-enolase significantly increased; moreover, these identical proteins are also found in stored, but not fresh, PRBCs, which may be used to resuscitate these injured patients (7;31). The function of α-enolase in conjunction with plasminogen in PMN-mediated lung injury and organ dysfunction is largely unexplored; while thrombin has been implicated in the activation of endothelial cells resulting in decreased barrier function and fibrin deposition, a hall mark of ALI/ARDS (3335). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, identical proteomic analyses of the plasma from rats that underwent hemorrhagic shock demonstrated that α-enolase significantly increased; moreover, these identical proteins are also found in stored, but not fresh, PRBCs, which may be used to resuscitate these injured patients (7;31). The function of α-enolase in conjunction with plasminogen in PMN-mediated lung injury and organ dysfunction is largely unexplored; while thrombin has been implicated in the activation of endothelial cells resulting in decreased barrier function and fibrin deposition, a hall mark of ALI/ARDS (3335). …”
Section: Discussionmentioning
confidence: 99%
“…Cortactin is ubiquitously expressed except for most hematopoietic cells and contains the following key domains: an N-terminal acidic domain that can bind to the Arp2/3 complex, an F-actin binding domain, a proline-rich region containing serine and tyrosine phosphorylation sites and a SH3 domain that mediates interaction with several proteins involved in actin polymerization (N-WASP), cell–cell adhesion (ZO-1) and membrane dynamics (dynamin) 16 17 18 . Cortactin can interact with myosin-light chain kinase (MLCK) in endothelial cells 19 20 , but a direct contribution of cortactin to MLC phosphorylation and actomyosin contractility has not been investigated. Instead, it has been shown that cortactin translocates to endothelial cell contacts in response to shear-stress where it may contribute to actin remodeling 21 .…”
mentioning
confidence: 99%
“…We utilized an established method for live cell imaging and kymograph analysis. 8 , 26 Briefly, EC grown on coverslips were loaded into a recording chamber (ALA Scientific Instruments, Westbury, NY, USA) in culture media at 37℃. Images were acquired by a Zeiss 710 laser scanning confocal microscope (every 6 s) and cells were observed under basal conditions and 10 min post administration of 1 μM S1P.…”
Section: Methodsmentioning
confidence: 99%
“…Images were analyzed using ImageJ and kymographic analysis was performed using the Multiple Kymograph Plugin to assess membrane dynamics as we have described previously. 8 , 26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation